Internal control of the organization and its external audit - L. V. Zavyalova; Financial University Brukhanenko (Вестник СибАДИ, 2017)
Internal control is one of the least studied types of financial control. However, in modern conditions it is crucial to the effective operation of the organization. In this article the authors have attempted, based on the analysis of various sources, to reveal the contents and rules of the auditor assessment of internal control. The article has interdisciplinary character, it is written at the intersection of financial control and audit. Special attention is focus on the internal controls and procedures of external auditing.